IMPACT OF SLEEP QUALITY ON WORKERS QUALITY OF LIFE: A CROSS-SECTIONAL STUDY IN THE SÃO PATRÍCIO VALLEY-GO (CIPEEX, 2024)
Sleep disorders are prevalent health problems in modern societies and significantly affect the quality of life (QoL). Sleep is essential for general health, accounting for around a third of the adult life time, and its poor quality is associated with a series of health problems and reduced QoL. This study aimed to assess the influence of sleeping on workers's quality of life in the São Patrício Valley - GO. This quantitative cross-sectional study was approved by the Research Ethics Committee under number 6.436.246. Using the questions “How satisfied are you with your sleep?” and “How would you rate your quality of life?” from the WHOQOL- BREF questionnaire. The data was analyzed using the SPSS software and the Chi-square test. A total of 704 workers were assessed, from which 62.2% were women ageing 39.1 years (±12.3). Among the participants, 41.3% were satisfied with their sleep and reported a good quality of life. On the other hand, 3.4% were dissatisfied with their sleep and reported poor quality of life, with a statistically significant difference (p=0.00). These results confirm the relationship between sleep quality and quality of life, highlighting the importance of strategies to improve sleep and, consequently, the QoL of workers. The study reinforces the need for interventions and policies that look forward to promoting better sleep habits and well-being in the workplace.
Keywords: sleep; quality of life; occupational health; worker